Chronic Kidney Disease: A Case Series (Advancements in Homeopathic Research, 2023)
Chronic renal failure (CRF) is a progressive and  irreversible deterioration of renal functions. Diabetes,  hypertension, indiscriminate use of antibiotics and  non-steroidal anti-inflammatory drugs (NSAIDs)  are major contributory factors of chronic kidney  disease (CKD) or end stage renal disease (ESRD). (1,2) In modern system, the role of medicinal treatment  is very limited while haemo or peritoneal dialysis  is cumbersome and expensive. Economic and  legal issues limit the possibility of renal transplant  and depends on the availability of donor.(3) On the  other hand, homoeopathic treatment, if sought at  an early stage, can help in maintaining or to some  extent reviving renal functions by lowering serum  creatinine thereby improving GFR. Gupta et. al. has  done some work on the medicinal treatment of this  difficult disease and have published the results.(4)
Keywords: Haemodialysis (HD); peritoneal dialysis (PD); chronic kidney disease (CKD); chronic renal failure (CRF); end stage renal disease (ESRD); serum urea; blood urea nitrogen (BUN); serum creatinine; estimated glomerular filtration rate (eGFR); renal transplant; homoeopathic treatment